2023
DOI: 10.1039/d3dt00150d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticancer mechanisms of zinc(ii)-8-hydroxyquinoline complexes with 1,10-phenanthroline ancillary ligands

Abstract: Twenty new zinc(II) complexes with 8-hydroxyquinoline (H-Q1–H-Q6) in the presence of 1,10-phenanthroline derivatives (D1–D10) were synthesized and formulated as [Zn(Q1)2(D1)] (DQ1), [Zn(Q2)2(D2)]·CH3OH (DQ2), [Zn(Q1)2(D3)] (DQ3), [Zn(Q1)2(D4)] (DQ4), [Zn(Q3)2(D5)] (DQ5), [Zn(Q3)2(D4)]...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 190 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Zinc is the second most abundant trace element inside the human body as well as an important biologically essential element . Zinc­(II) complexes appeared to be appealing as anticancer metallodrugs because these complexes are less toxic even at higher dosages than other heavy metals. Recently, many Zn­(II) complexes have been developed for anticancer applications. Among these complexes, the curcumin-based Zn­(II) complexes exhibited significant in vitro anticancer activities. For example, Pucci et al reported the cytotoxicity of Zn­(II)-curcumin complexes of bipyridine derivatives toward a human neuroblastoma cell line (SH-SY5Y) under dark conditions . Zhang et al reported the Zn­(II) curcumin complex of tryptanthrin and cryptolepine–cyclen derivatives showing good anticancer activity against A549 cells. , In a similar study, Liang’s group found that the cryptolepine derivative of the Zn­(II) curcumin complex was more active than cisplatin against T-24 cells .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is the second most abundant trace element inside the human body as well as an important biologically essential element . Zinc­(II) complexes appeared to be appealing as anticancer metallodrugs because these complexes are less toxic even at higher dosages than other heavy metals. Recently, many Zn­(II) complexes have been developed for anticancer applications. Among these complexes, the curcumin-based Zn­(II) complexes exhibited significant in vitro anticancer activities. For example, Pucci et al reported the cytotoxicity of Zn­(II)-curcumin complexes of bipyridine derivatives toward a human neuroblastoma cell line (SH-SY5Y) under dark conditions . Zhang et al reported the Zn­(II) curcumin complex of tryptanthrin and cryptolepine–cyclen derivatives showing good anticancer activity against A549 cells. , In a similar study, Liang’s group found that the cryptolepine derivative of the Zn­(II) curcumin complex was more active than cisplatin against T-24 cells .…”
Section: Introductionmentioning
confidence: 99%
“…11 In the human body, zinc is the second most abundant metal ion essential for several biochemical processes, such as enzyme regulation, gene expression, neurotransmission, and apoptosis. 12–14 Zinc at average concentration controls various biological, environmental, and metabolic processes. At the same time, a deficiency of zinc leads to some clinical diseases, such as brain dysfunction, high blood cholesterol, growth retardation, ischemic stroke, Parkinson's disease, Alzheimer's disease, etc.…”
mentioning
confidence: 99%